Mapping and Preserving the Visuospatial Network by repetitive nTMS and DTI Tractography in Patients With Right Parietal Lobe Tumors - Raffa, Giovanni; Quattropani, Maria Catena; Marzano, Giuseppina; Curcio, Antonello; Rizzo, Vincenzo; Sebestyén, Gabriella; Tamás, Viktória; Büki, András; Germanò, Antonino (Frontiers in Oncology, 2021)
Introduction: The identification of functional networks involved in complex brain functions, including visuospatial abilities (VSAs), is usually difficult. We report our preliminary experience using a preoperative planning based on the combination of navigated transcranial magnetic stimulation (nTMS) and DTI tractography to provide the preoperative 3D reconstruction of the visuospatial (VS) cortico-subcortical network in patients with right parietal lobe tumors. Material and Methods: Patients affected by right parietal lobe tumors underwent mapping of both hemispheres using an nTMS-implemented version of the Hooper Visual Organization Test (HVOT) to identify cortical areas involved in the VS network. DTI tractography was used to compute the three branches of the superior longitudinal fasciculus (SLF). The 3D reconstruction of the VS network was used to plan and guide the safest surgical approach to resect the tumor and avoid damage to the network. We retrospectively analysed the cortical distribution of nTMS-induced errors, and assessed the impact of the planning on surgery by analysing the extent of tumor resection (EOR) and the occurrence of postoperative VSAs deficits in comparison with a matched historical control group of patients operated without using the nTMS-based planning (Group B). Results: Twenty patients were enrolled in the study (Group A). The error rate (ER) induced by nTMS was higher in the right vs. left hemisphere (p=0.02). In the right hemisphere, the ER was higher in the anterior supramarginal gyrus (aSMG) (1.7%), angular gyrus (1.4%) superior parietal lobule (SPL) (1.3%), and dorsal lateral occipital gyrus (dLoG) (1.2%). The reconstruction of the VS network was successfully used to plan and guide tumor resection. We observed a significantly improved postoperative HVOT score in Group A vs. Group B (p=0.03), while no differences were recorded for the EOR. Conclusions: The nTMS-implemented HVOT is a feasible approach to map cortical areas involved in VSAs. It can be combined with DTI tractography, thus providing a reconstruction of the VS network that could guide neurosurgeons to preserve the VS network during tumor resection, thus reducing the occurrence of postoperative VSAs deficits as compared to standard asleep surgery.